2011
DOI: 10.1111/j.1753-4887.2011.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between biomarker-quantified antioxidant status during pregnancy and infancy and allergic disease during early childhood: A systematic review

Abstract: Recent findings suggest a significant association between the antioxidant status of pregnant women and of their children during the first years of life and the development of allergic disease during childhood. The aim of this review was to identify all studies that estimated the effect of intake of antioxidants in pregnant women and their children on the development of allergic disease during early childhood. A systematic review was conducted of epidemiological studies featuring original peer-reviewed data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…There is increasing evidence of an association between VAD and airway hyperresponsiveness, defined as an exaggerated contraction of the bronchial smooth muscle (SM) in response to environmental or pharmacological stimuli (11)(12)(13)(14). These studies have also shown that maternal VAD has a negative impact on postnatal lung function in children, which can be alleviated by proper supplementation during gestation (15,16).…”
Section: Introductionmentioning
confidence: 94%
“…There is increasing evidence of an association between VAD and airway hyperresponsiveness, defined as an exaggerated contraction of the bronchial smooth muscle (SM) in response to environmental or pharmacological stimuli (11)(12)(13)(14). These studies have also shown that maternal VAD has a negative impact on postnatal lung function in children, which can be alleviated by proper supplementation during gestation (15,16).…”
Section: Introductionmentioning
confidence: 94%
“…The consumption of peanuts and tree nuts also provides an important source of specific immunomodulatory nutrients that have been independently associated with allergic risk, including polyunsaturated fatty acids, selenium, zinc, folate, vitamin E, and other antioxidants. [5][6][7] It is also possible that the dietary patterns associated with higher nut consumption could also be associated with higher consumption of vegetables, fruits, and legumes. For example, dietary patterns, such as a Mediterranean diet during pregnancy, have been associated with protection against childhood asthma and wheeze, 6 in particular higher consumption of vegetables, legumes, and fish.…”
mentioning
confidence: 96%
“…However, some of the studies were not able to establish the role of selenium (15,16). Nonetheless, epidemiological studies suggest that Se has beneficial immunomodulatory properties and Se supplementation may reduce allergic asthma (17)(18)(19)(20)(21). In our previous studies, oral Se supplementation was found to change immune responses from Th2-type to Th1/T reg -types, which modulates levels of asthma in mice (22,23).…”
Section: Introductionmentioning
confidence: 99%